Effect of Ethanol Treatment on Characteristics of Micro-Porous Silicon Based Hydrogen Fuel Cells - Yuksel, Sureyya Aydin; Dzhafarov, Tayyar D.; Nuhoglu, Cigdem; Korpeoglu, F. Dilara; Topkaya, Ramazan (AMER SCIENTIFIC PUBLISHERS, 2018)
The objective of this paper is reporting the results on Fourier transform infrared (FTIR) and electron paramagnetic resonance (EPR) spectra of ethanol-treated micro porous silicon (PS) membrane and its influence on electrical parameters of Au/PS/Si direct ethanol fuel cells. PS layers have been prepared on n-type silicon using the anodic etching under illumination. PS/Si before Au deposition was kept in ethanol solution for 24 h to oxidize the extended pore surfaces. Increase of the open-circuit voltage and the short-circuit current for Au/PS/Si fuel cell with ethanol-treated PS membrane bed with ethanol by factor of 6-10 in compared to that of untreated membrane was observed. Improvement of the electrical parameters of Au/PS/Si cells is attributed to oxidized effect of ethanol treatment resulting in increased concentration of dangling bonds on pore surfaces and increase of proton conductivity of PS membrane.
Keywords: Porous Silicon; Fuel Cell; DEFC; EPR; PHOTOLUMINESCENCE; OXIDATION; Materials Science